Computational and Experimental Insights into Asymmetric Rh‐Catalyzed Hydrocarboxylation with CO2. Issue 4 (12th January 2021) - Pavlovic, Ljiljana; Pettersen, Martin; Gevorgyan, Ashot; Vaitla, Janakiram; Bayer, Annette; Hopmann, Kathrin H.
Abstract: The asymmetric Rh‐catalyzed hydrocarboxylation of α, β‐unsaturated carbonyl compounds was originally developed by Mikami and co‐workers but gives only moderate enantiomeric excesses. In order to understand the factors controlling the enantioselectivity and to propose novel ligands for this reaction, we have used computational and experimental methods to study the Rh‐catalyzed hydrocarboxylation with different bidentate ligands. The analysis of the C−CO2 bond formation transition states with DFT methods shows a preference for outer‐sphere CO2 insertion, where CO2 can undergo a backside or frontside reaction with the nucleophile. The two ligands that prefer a frontside reaction, StackPhos and t Bu‐BOX, display an intriguing stacking interaction between CO2 and an N‐heterocyclic ring of the ligand (imidazole or oxazoline). Our experimental results support the computationally predicted low enantiomeric excesses and highlight the difficulty in developing a highly selective version of this reaction. Abstract : Computational and experimental methods were employed to study the potential of different bidentate ligands in the enantioselective Rh‐catalyzed hydrocarboxylation of acrylates. Our computational analysis shows that during C−C bond formation, CO2 prefers an outer sphere insertion mode. The ligands StackPhos and t Bu‐BOX show good yields and display an intriguing stacking interaction between the internal N‐heterocycle and CO2.